Basic cybersecurity protocol for SMES - Bustillos Ortega, Olda (2022)
Movement restrictions imposed by governments during the COVID-19 pandemic have changed consumption patterns and the way of doing business, forcing small and medium-sized companies to migrate their businesses to electronic media. Similarly, crime increased its participation in cyberspace, exploiting the vulnerability of these companies due to their dependence on digital technologies and the lack of resources for effective management of data integrity, confidentiality, and availability. Therefore, it is necessary to sensitize small and medium- sized companies about the importance of cybersecurity and prepare them not only to defend themselves against cyberattacks but also for a quick and timely recovery from possible incidents. The objective of this study is to propose a basic cybersecurity protocol as the primary defense strategy against cyberattacks, which allows business continuity in the event of a cyberattack. Academic publications, theses, technical standards, and practical guides examined in the current global threats context were the protocol’s basis. Small and medium-sized companies perceive cybersecurity as too complex and onerous; thus, they require economical, effective, and accessible solutions.